Vegetative, endocrine and metabolic accompaniments of individual immune responses to adaptogenic balneotherapy - Mel’nyk, Oksana; Struk, Zoryana; Zukow, Walery; Popovych, Igor (Journal of Education, Health and Sport, 2019)
Background. Earlier in clinical observations four variants of the immune responses to adaptogenic balneotherapy at the Truskavets’ spa have been identified. In 40,9% of patients, initially normal immune status did not change significantly; in 31,8%, the lower boundary level of immunity is completely normalized; in 22,7% moderate immunosuppression is reduced, but not up to normal; however, in 4,5% of people, initially normal level of immunity are transformed into moderate immunosuppression. All four variants of immune responses are virtually unmistakably predicted by a set of 20 predictors. The purpose of this study is to analyze vegetative, endocrine and metabolic accompaniments of individual immune responses to balneofactors of Truskavets’ spa. Material and methods. The object of observation were 34 men and 10 women aged 24-70 years old, who came to the Truskavets’ spa for the treatment of chronic pyelonephritis combined with cholecystitis in remission. The survey was conducted twice, before and after balneotherapy (drinking bioactive water Naftussya three times a day, ozokerite applications, mineral baths every other day for 7-10 days). Immune status evaluated on a set of I and II levels recommended by the WHO. The state of the autonomic nervous system is estimated by HRV ("CardioLab+HRV"). To assess endocrine status we determined plasma levels of principal adaptation Hormones: Cortisol, Testosterone and Triiodothyronine (ELISA). We determined also the plasma and daily urine levels of the electrolytes: calcium, phosphates, sodium, potassium, magnesium and chloride as well as nitrous metabolites creatinine, urea and uric acid. According to the parameters of electrolyte exchange, parathyroid, calcitonin and mineralocorticoid hormonal activities was evaluated. We estimated also plasma lipide spectrum. Results. 13 immunosuppressive and 6 immune-enhancing neuro-endocrine and metabolic parameters identified. Discriminant analysis conducted to identify parameters, in which the four immune response clusters differ significantly from each other. 25 parameters are characteristic, 12 of them related to the HRV, 5 to endocrine, 5 to electrolytes and 3 to nitrous metabolites exchange. Conclusion. Individual immune responses to adaptogenic balneofactors are accompanied by characteristic changes in the parameters of the autonomic nervous and endocrine systems, as well as the exchange of electrolytes, nitrogen metabolites and lipids.